Transition of renewable energy policies in Malaysia: benchmarking with data envelopment analysis - Mohd Chachuli, Fairuz Suzana (Elsevier, 2021)
Using data envelopment analysis (DEA) and Malmquist index (MI) method, this study investigates the effect of the transition of renewable energy operational policies in Malaysia through static and dynamic analyses. This study also evaluates the performance of the country's operational policies in the development of renewable energy including small renewable energy power (SREP), feed-in tariff (FiT), large-scale solar photovoltaic (LSSPV) and net energy metering. In this study, three inputs (employment, electricity generation and renewable energy licensed capacity) and two outputs (gross domestic product and renewable energy generation) are used. Using the panel dataset, this study applies the Malmquist productivity index to calculate the changes in efficiency, technology and total productivity in four Malaysian regions in 2010–2017. Results show that the East Malaysia region is the most efficient in developing renewable energy during the aforementioned period. Results also demonstrate that Malaysia experienced a decrease in renewable energy efficiency during the first policy transition from the SREP programme to the FiT programme, and efficiency increased during the second policy transition from the FiT programme to the integrated programme in 2017. Malaysia's renewable energy policy transition has also contributed up to sevenfold of social benefits in solar photovoltaic industry job creations between 2012 and 2019, and up to 0.16% in carbon emission reduction of environmental impacts from 2012 to 2018. Using DEA and the MI method, this study highlights the phase of transition of renewable energy policies and the effect of implementing these policies on renewable energy development in Malaysia.